Weather-Resistance Bench Inspired by Young Badminton Logo - Kek, Zi Jian; Selimin, Mohamad Ali (Research in Management of Technology and Business, 2023)
All year long, as a tropical country, it is hot and humid in Malaysia. An outdoor bench kept outside the roof will not endure for very long since the bench’s material can become tarnished from exposure to moisture and harsh direct sunlight. As a result, the weather had numerous consequences that damaged outdoor furniture, making upkeep or buying new outdoor furniture expensive. Therefore, the purpose of this study is to define the criteria for designing and developing a prototype for a weather-resistant bench that draws its inspiration from the YOUNG badminton logo. A quantitative survey using Google Forms was carried out to establish the design criteria. A total of 50 individuals were surveyed who visitors at Taman Rekreasi Tasik Y in Batu Pahat, Johor. According to the analysis, the majority of respondents believe that rust is the most frequent type of bench damage, and 100% of respondents prefer benches that are resistant to the elements. Findings indicate that a bench in a leisure area must have a modern style design, be natural in colour, and be composed of a mix of mild steel and wood. The bench design was produced using the design requirements generated from the survey. The bench design process then proceeded to begin with visual research, 30 thumbnails, 6 ideation, and 4 idea development prior to the final design selection. Subsequently, mock-up and technical drawings were generated based on the selected final design. The prototype’s construction materials included Chengal wood and mild steel with shellac and lacquer as finishing for wood materials. In summary, this research’s design can make outdoor furniture more resistant to weather issues including exposure to water, moisture, and sunlight. Unprotected wooden furniture can warp and suffer other damages.